Dynamic wind speed model for solving wind power problems - Obukhov, S.G.; Plotnikov, I.A.; Masolov, V.G. (KU publ., 2020)
This work is devoted to the development of a dynamic model of wind speed designed to solve the problems of wind power. The time model of wind is presented in the form of two components - constant and turbulent. The Kaimal spectral model recommended by IEC 61400-1:2005 is used to describe the turbulent component of wind speed. The initial data for the calculation of turbulence parameters are the class of wind power plant, which is determined by its location, the height of the axis of rotation of the wind wheel and the average wind speed for the specified time interval of simulation. Computer implementation of wind model is carried out on the basis of statistically independent sources of white noise acting on forming filters, output signals of which are summed. The analysis of the obtained results shows that the wind flow model implemented on the basis of the method of forming filters provides adequate modeling of the longitudinal component of wind speed and can be used to solve the problems of wind power engineering.
Жел энергетикасының есептерін шешу үшін жел жылдамдығының динамикалық моделі
Динамическая модель скорости ветра для решения задач ветроэнергетики
Keywords: wind power; wind model; spectral model; forming filters